C-geranylated flavonoids from Paulownia tomentosa Steud. fruit as potential anti-inflammatory agents - Molčanová, Lenka; Treml, Jakub; Brezáni, Veronika; Maršík, Petr; Kurhan, Sebnem; Trávníček, Zdeněk; Uhrin, Pavel; Šmejkal, Karel (Journal of ethnopharmacology, 2022)
ETHNOPHARMACOLOGICAL RELEVANCE: Paulownia tomentosa Steud., a traditional Chinese medicinal plant, was used for many centuries in Chinese herbal medicine as a component of remedies for many illnesses, including inflammatory diseases. It is a rich source of phenolic compounds, mainly geranylated flavonoids, which are currently studied for their promising biological activities. AIM OF THE STUDY: The study aimed to isolate minor geranylated flavanones and flavones from P. tomentosa fruit and evaluate their cytotoxicity and possible anti-inflammatory effects in a cell-based model of inflammation. MATERIALS AND METHODS: Chromatographic separation of chloroform portion of the ethanolic extract of P. tomentosa fruit led to the isolation of twenty-seven flavonoids (1-27), twenty-six of them geranylated with different modifications and one non-geranylated flavanone, and two phenolic compounds. Compounds were identified using UV, IR, HRMS, NMR, and CD spectroscopy. Ten of these compounds (7-10, 12, 21, 22, 24, 25, and 27) were determined to be new flavonoid derivatives obtained from a natural source for the first time. Selected compounds were analyzed for cytotoxicity and anti-inflammatory potential to affect the activation of nuclear factor κB/activator protein 1 (NF-κB/AP-1) after lipopolysaccharide (LPS) stimulation. RESULTS: All the test compounds (1-21 and 23-26) reduced the activation of NF-κB/AP-1 24 h after the addition of LPS. Eight compounds (5, 14-18, 21, and 26) were more active than prednisone, a widely used anti-inflammatory drug. However, this effect was not seen significantly on the level of TNF-α and IL-1β, which can be explained by the plurality of possible outcomes of activation of the NF-κB pathway in cells. CONCLUSIONS: Results of the presented study confirmed that constituents from traditional Chinese medicinal plant P. tomentosa Steud. have promising anti-inflammatory activities and can serve as a potential source of inspiration for new anti-inflammatory medications.
Keywords: Flavonoids; rostlinné extrakty; Plant Extracts; flavonoidy; antiflogistika; ovoce; léčivé rostliny; hluchavkotvaré; NF-kappa B; transkripční faktor AP-1; Lamiales; lipopolysacharidy; Plants, Medicinal; Transcription Factor AP-1; Anti-Inflammatory Agents; Lipopolysaccharides; Fruit